The Effect of Manager-Employee Interpersonal Communication Effectiveness and Organizational Communication Climate on the Employee Performance in the Working Area of the Directorate General of State’s Asset Office of North Sumatera - Sibuea, Perasanta (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The objective of the research is to analyze the effectiveness of manager-employee interpersonal communication and organizational communication climate on the employee performance in the working area of the Directorate General of State’s Assets Office of North Sumatera. The theories used are the theory of perspective humanism in the effectiveness of interpersonal communication suggested by Joseph A. Devito, the theory of communication climate dimension suggested by Redding, and the theory of employee performance suggested by Bernardin and Russel. The total population of the research is 169 employees, and the total samples are 118 employees taken using proportional sampling technique from 5 offices in the working area of the Directorate General of State’s Asset Office of North Sumatera. The research employs the correlation method which is gathering the data by distributing questionnaires and analyzing it by using multiple linear regression tests. The results of the research show that manager-employee interpersonal communication effectiveness has significant effects on employee performance, organizational communication climate has significant effects on employee performance, and both manager-employee interpersonal communication effectiveness and organizational communication climate have significant effects on employee performance. Manager-employee interpersonal communication effectiveness and organizational communication affect 83.2% of employee performance. There are many factors not used in this study like office distances from home base, years of services, achievement motivation, level of income, and others. Good manager-employee communication and a conducive communication climate will increase employee performance.